2018
DOI: 10.1113/jp276459
|View full text |Cite
|
Sign up to set email alerts
|

Increased human stretch reflex dynamic sensitivity with height‐induced postural threat

Abstract: Postural threat increases soleus tendon-tap (t-) reflexes. However, it is not known whether t-reflex changes are a result of central modulation, altered muscle spindle dynamic sensitivity or combined spindle static and dynamic sensitization. Ramp-and-hold dorsiflexion stretches of varying velocities and amplitudes were used to examine velocity- and amplitude-dependent scaling of short- (SLR) and medium-latency (MLR) stretch reflexes as an indirect indicator of spindle sensitivity. t-reflexes were also performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 58 publications
3
39
0
Order By: Relevance
“…Neuro-anatomical evidence for direct influences of emotion onto balance control systems has been well-established in animal models ( 83 , 85 , 86 ). Supporting evidence has been established in standing humans, with threat-induced increases observed in: (1) muscle-spindle sensitivity ( 56 , 57 , 87 ); (2) 1b reflex gain ( 65 ); and (3) vestibular gain of balance, head and eye-reflexes ( 60 63 , 66 ). While early cortical potentials seem unaffected by threat ( 55 , 56 ), later cortical changes thought to be responsible for processing sensory information are significantly influenced with threat ( 44 , 55 , 88 ).…”
Section: Potential Mechanisms Underlying Threat-related Postural Chanmentioning
confidence: 69%
“…Neuro-anatomical evidence for direct influences of emotion onto balance control systems has been well-established in animal models ( 83 , 85 , 86 ). Supporting evidence has been established in standing humans, with threat-induced increases observed in: (1) muscle-spindle sensitivity ( 56 , 57 , 87 ); (2) 1b reflex gain ( 65 ); and (3) vestibular gain of balance, head and eye-reflexes ( 60 63 , 66 ). While early cortical potentials seem unaffected by threat ( 55 , 56 ), later cortical changes thought to be responsible for processing sensory information are significantly influenced with threat ( 44 , 55 , 88 ).…”
Section: Potential Mechanisms Underlying Threat-related Postural Chanmentioning
confidence: 69%
“…Another possibility is that the stretch reflex increases, leading to stronger counter-acting forces produced against the perturbation. For instance, the stretch reflex is sensitive to cognitive factors such as standing next to a void (Horslen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, some threat-induced changes in behaviour may be associated with state-related changes not measured in the present study. For example, it has been shown that there are broad, multi-sensory changes when individuals are exposed to height-induced threat, whereby balance relevant proprioceptive 4144 and vestibular 4547 reflexes are facilitated. It is unclear if these changes in sensory processing scale linearly with individuals’ emotional response to threat.…”
Section: Discussionmentioning
confidence: 99%